2021
DOI: 10.3389/fphys.2021.619054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Low Hemoglobin on Body Composition, Strength, and Redox Status of Older Hemodialysis Patients Following Resistance Training

Abstract: IntroductionThe purpose of this study was to: (i) investigate the effect of six months of resistance training (RT) on body composition, muscle strength, hematological patterns, and redox profile in maintenance hemodialysis (HD) patients, and; (ii) evaluate the effects of baseline concentrations of hemoglobin on the RT response.MethodsOne hundred fifty-seven subjects with chronic kidney disease (CKD) were randomly allocated into two groups: Control [CTL, (n = 76)] and RT (n = 81). A first visit was required for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
8
1
Order By: Relevance
“…Among the 49 studies, 2 studies were excluded due to their ineligible interventions, 1 study was excluded because of its ineligible language, and 27 studies were excluded because of their ineligible comparators. Eventually, 7 studies were included in the systematic review ( Alghadir et al, 2016 ; Campbell et al, 2010 ; da Silva et al, 2021 ; Dani et al, 2020 ; Fatouros et al, 2004 ; Osali, 2020 ; Vincent et al, 2002 ). The flow diagram was presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the 49 studies, 2 studies were excluded due to their ineligible interventions, 1 study was excluded because of its ineligible language, and 27 studies were excluded because of their ineligible comparators. Eventually, 7 studies were included in the systematic review ( Alghadir et al, 2016 ; Campbell et al, 2010 ; da Silva et al, 2021 ; Dani et al, 2020 ; Fatouros et al, 2004 ; Osali, 2020 ; Vincent et al, 2002 ). The flow diagram was presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported the effects of exercise therapy on anemia as well as the relationship between anemia and muscle weakness [ 26–28 ]. Treatment of anemia is an important factor in improving frailty in healthy people [ 13 ], and resistance training for muscle strength was reported to improve HGS and Hb levels in patients undergoing HD [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines for renal rehabilitation, published by the Japanese Society of Renal Rehabilitation in 2018 note that exercise therapy is reported to be effective for improving exercise tolerance, QoL, dialysis efficiency, and ADL, preventing and improving protein-energy wasting, inhibiting protein catabolism, and preventing cardiovascular disease [ 15 ]. To avoid the risk of CVD in patients receiving high-dose ESA treatment [ 25 ], improvement of anemia by exercise treatment [ 26 , 28 ] might be useful.…”
Section: Discussionmentioning
confidence: 99%
“…Because of that, ESA and iron supplementation may be considered to improve health-related parameters in this population [ 1 , 2 ]. RT has appeared as a non-pharmacological therapy to improve iron metabolism in this population [ 6 , 8 , 17 ]. The possibility of using RT as part of the treatment of iron deficiency may lead to relevant management of anemia biomarkers ( Figure 2 and Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, 72.61% of the patients underwent EPO treatment (control group (CTL) = 69.73%; resistance training group (RT) = 75.30%) and 54.14% underwent oral iron supplementation (CTL = 55.26%; RT = 53.08%). Given that both treatments may influence multifactorial pathways related to inflammation and iron status, and RT is an important regulator of both aforementioned factors [ 6 , 7 , 8 , 9 ], two fundamental questions are raised here: (I) Does RT enhance the treatment with EPO and iron sulfate in ESRD older individuals? (II) Is RT an effective treatment on its own to improve iron status?…”
Section: Introductionmentioning
confidence: 99%